The impact of environmental and social factors on learning abilities: a meta‐analysis. (3rd August 2021) - Lambert, Connor T.; Guillette, Lauren M.
ABSTRACT: Since the 1950s, researchers have examined how differences in the social and asocial environment affect learning in rats, mice, and, more recently, a variety of other species. Despite this large body of research, little has been done to synthesize these findings and to examine if social and asocial environmental factors have consistent effects on cognitive abilities, and if so, what aspects of these factors have greater or lesser impact. Here, we conducted a systematic review and meta‐analysis examining how different external environmental features, including the social environment, impact learning (both speed of acquisition and performance). Using 531 mean‐differences from 176 published articles across 27 species (with studies on rats and mice being most prominent) we conducted phylogenetically corrected mixed‐effects models that reveal: ( i ) an average absolute effect size | d | = 0.55 and directional effect size d = 0.34; ( ii ) interventions manipulating the asocial environment result in larger effects than social interventions alone; and ( iii ) the length of the intervention is a significant predictor of effect size, with longer interventions resulting in larger effects. Additionally, much of the variation in effect size remained unexplained, possibly suggesting that species differ widely in how they are affected by environmental interventions due to varying ecological and evolutionary histories. Overall our results suggest that social and asocial environmental factors do significantly affect learning, but these effects are highly variable and perhaps not always as predicted. Most notably, the type (social or asocial) and length of interventions are important in determining the strength of the effect.